Feminist fight club : an office survival manual (for a sexist workplace) - Bennett, Jessica, 1981- (Harper Wave, an imprint of HarperCollins Publishers, 2016)
"Part manual, part womanifesto, Feminist Fight Club is a hilarious yet incisive guide to navigating subtle sexism at work, providing real-life career advice and humorous reinforcement for a new generation of professional women"--